Indagaciones encarnadas sobre el deseo de irse de las mujeres rurales jóvenes - Iraide Álvarez-Muguruza (Revista Iberoamericana de Estudios de Desarrollo)
In this paper, it is tried to approach the reality of Sayago (Zamora), in order to investigate the elements that affect the construction of the desire to leave rural areas through the relationship between girls and space, because they are understood as a significant dimensions by focusing on the discursive constructions, images and perceptions of young rural women about their home village. In this way, the results show that the experience of young rural women reflects an affective topology and rhythms that arises from the relationship between their bodily hexis and the geographical spaces in which they are situated. These processes are intrinsical to their subjectivities, and they structure the way in which this youth women sail in their future, so that, when the cultural ideals that sustain life in the village cease to be desirable, the urban life model is imposed as valid in its imaginary.